Synaptic dysfunction in human immunodeficiency virus type‐1‐positive subjects: inflammation or impaired neuronal plasticity? - Avdoshina, V.; Bachis, A.; Mocchetti, I. (Journal of internal medicine, 2013)
Many people infected with the human immunodeficiency virus type‐1 (HIV) exhibit mild or severe neurological problems, termed HIV‐associated neurocognitive disorder (HAND), even when receiving antiretroviral therapy. Thus, novel adjunctive therapies must be developed to overcome the neurotoxic effect of HIV. New therapies require a better understanding of the molecular and cellular mechanisms of HIV‐induced neurotoxicity and the risk factors that, besides inflammation and T‐cell depletion and drugs of abuse, render the central nervous system (CNS) a target of HIV‐induced neurotoxicity. HIV appears to impair neuronal plasticity, which refers to the innate ability of the CNS respond to injury and promote recovery of function. The availability of brain‐derived neurotrophic factor (BDNF), a potent neurotrophic factor that is present in abundance in the adult brain, is essential for neuronal plasticity. BDNF acts through a receptor system composed of Trk and p75NTR. Here, we present experimental evidence that some of the clinical features of HIV‐mediated neurological impairment could result from altered BDNF/TrkB/p75NTR regulation and function.